Pielonefritis Akut: Diagnosis dan Tatalaksana - Salsabila Nurislami; Exsa Hadibrata; Bayu Anggileo Pramesona; Rasmi Zakiah Oktarlina (MAJORITY, 2023)
Acute pyelonephritis is a severe urinary tract infection (UTI) in the upper urinary tract. The incidence of acute pyelonephritis in the world has increased. Each year, it is estimated that 1 in 830 people in the UK develop pyelonephritis. Approximately 80-90% of cases of acute pyelonephritis are caused by Escherichia coli bacteria. Catheter insertion predisposes to infection with gramnegativebacteria such as Proteus, Klebsiella, Serratia, or Pseudomonas. The onset of symptoms can vary for each individual from hours to days and the severity of the disease also varies. Symptoms of acute pyelonephritis are flank pain, fever and nausea. The results of the physical examination of the patients also varied from looking sick and uncomfortable to looking healthy, there was bilateral costovertebral angle pain, and suprapubic pain with or without off pain. Examination to confirm the diagnosis is a urine culture with results showing the growth of uropathogens of 10,000 colony units per milliliter of urine. The management of pyelonephritis includes three pillars, namely supportive care with fluid and drug resuscitation, effective antibiotic therapy, and control with imaging in indicated patients.